The pollen morphology of Nigerian bignoniaceae Juss (2007)
The Pollen grains of eleven species of the Bignoniaceae represented in Nigeria have been studied by the light Microscope. The pollen grains are mostly circular or elliptic. The circular ones include those of Crescentia cujete Linn. Markhamia tomentosa (Benth.) K.Schum., Newbouldia laevis Seem., Oroxyllum indicum Vent., Spatliodea campanulata P.Beauv., Stereospermum acuminatissimum K.Schum., Stereospermum kunthianum Cham., and Tabebuici rosea (Berthol) DC. while the Elliptic ones are: Kigali a africana (Lam) Benth., Markhamia litlea (Benth.) K.Schum. and Tecoma stans (Linn ) H.B & K. and the shape/class range from prolate, sub-prolate to prolate spheroidal. The Prolate ones are Kigelia africana, Markhamia tomentosa, and Tecoma stans; the Subpralate types includes those of Crescentia cujete, Markhamia lutea, OroxyUum indicum. Spathodea campanulata and Stereospermum acuminatissimum; while the Prolate-Spheroidal types are those of Stereospermum kunthianum and Tabebuia rosea. They are either tefra- colporate or tri-colporate. The pollen of Crescentia cujete is Tetra-Colporaie while tiic others are Tri-colporate (Tri-colporate = Pollen grains with three ectocolpi;). The different pollen types are useful in the identification of the Nigerian Bignoniaceae.